ABOUT MODERNIZATION TENDENCIES IN THE LEGAL SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Ayupova Z.K.; Kussainov D.U.; Nagan Winston (Scientific Journal of Pedagogy and Economics, 2019)
The legal system of any state should be considered in close connection with other national legal systems and with international law. Such a “legal triangle” serves as a common legal space, in which different normative legal arrays interact, collide, and coexist. And in this relationship there is a lot of sustainable and regular, controversial and random. It is based on common integrative processes, strengthening cooperation of states in the economic, social, cultural and other spheres. The Constitution of Uzbekistan of 1992 has assigned an important place in the legal system to international law. In the modern period, when intensive work is underway to improve Uzbek legislation, the use of methods of both domestic and international legal regulation is required. In state law, these are the constitutional foundations of foreign policy, the competence of the supreme bodies of state power in the sphere of international relations, the regulation of citizenship, the rights and freedoms of the individual. In the civil and family law, civil proceedings are both traditional issues of private international law, legal assistance in civil and family matters, improvement of foreign economic relations, received particular relevance. In the criminal law and criminal proceedings are multidimensional aspects of cooperation in the fight against crimes, providing legal assistance in the criminal matters.